Reduction of tungsten oxides with carbon and hydrogen - Venables, Dean Stuart (Rhodes University, Faculty of Science, Department of Chemistry, 1996)
The reductions of WOâ‚ƒ with hydrogen, with CO, and with carbon, as well as the reduction of WOâ‚ƒ/graphite mixtures with hydrogen, were studied using thermogravimetry, evolved gas analysis, X-ray powder diffraction, and scanning electron microscopy. The intermediate phases Wâ‚‚â‚€Oâ‚…â‚ˆ, Wâ‚ â‚ˆOâ‚„â‚‰ and WOâ‚‚, were observed in the reductions. The final product of the reductions with hydrogen and carbon was tungsten, and we was formed in the reduction with CO. The reaction paths in the overall processes were determined. The reactant/product gas ratio had a considerable influence on which reactions took place. The morphology of the sample was characterised at different stages of the reduction. The shape of the WOâ‚ƒ particles was retained during the reduction. Particle growth was observed in the reduction with hydrogen and was attributed to the formation of WOâ‚‚(OH)â‚‚(g). The kinetics of the reductions were investigated , and the reaction mechanisms determined. The reduction of WOâ‚ƒ with CO was studied from 650 to 900Â°C, and occurred at a phase boundary with an activation energy of 40 kJ molâ »Â¹ . The reduction of WOâ‚‚, was studied under the same conditions. The reaction also occurred at a phase boundary and had an activation energy of 62 kJ molâ »Â¹. The reduction of WOâ‚ƒ with carbon was studied from 935 to 1100Â°C and took place via CO and COâ‚‚. Two stages were observed in the reduction . The first stage, which corresponded approximately to the formation of WOâ‚‚ had an activation energy of 66 kJ molâ »Â¹ and was limited by diffusion through the porous reacting particles. The second stage was first order and had an activation energy of 40 kJ molâ »Â¹. The reduction of WOâ‚ƒ and WOâ‚ƒ graphite mixtures with hydrogen were studied from 575 to 975 Â°C. The reactions were controlled by mass-transfer under the conditions investigated. The addition of carbon increased the rate of the reduction process , but did not affect the phases formed in the system. COâ‚‚ was evolved mainly at the start, and CO mainly at the end of the process.
Keywords: Oxidation-reduction reaction; Tungsten; Hydrogen; Carbon